Tinjauan Yuridis terhadap Pemenuhan Hak Asasi Anak atas Keamanan Pangan dalam Program Makan Bergizi Gratis (MBG) di Kepulauan Riau - Anjawai, Namrysilia Buti; Permatasari, Rika; Rachmadhanto, Dimas Adam Satrio; Simanjuntak, Fhlorida Agustina (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The Free Nutritious Meal Program (MBG) serves as a concrete instrument for the government to fulfill children's fundamental rights to adequate food, supporting their physical and mental development. However, the implementation of this program in the Riau Islands faces serious challenges, evidenced by food poisoning cases in several schools, such as SMPN 2 Karimun, which threaten student safety. This research aims to analyze the legal standing of food safety as a child's right within national and international frameworks and evaluate its implementation in the MBG program in the Riau Islands. Using normative legal research with a juridical approach, this study examines various regulations ranging from the 1945 Constitution to the Convention on the Rights of the Child. The results indicate that while regulations establish strict standards through the Food Law and National Nutrition Body (BGN) guidelines, many Nutrition Fulfillment Service Units (SPPG) in the Riau Islands have not yet obtained the Food Sanitation Hygiene Certificate (SLHS). Stronger supervision across all stages—from ingredient selection to distribution—and accelerated facility certification are required to ensure that children's rights to food safety are fulfilled tangibly and consistently.